Evolução dos canais fluviais: morfometria e sedimentologia na bacia hidrográfica do rio Santo Antônio, Serra da Canastra – MG - Araújo, Marina Silva (2017)
The work in question deals with morphometric and granulometric analyzes in the Santo Antônio River Basin in order to better understand the fluvial and geomorphological dynamics in the Serra da Canastra region, Minas Gerais. The morphometric indices were developed in a GIS environment using the ArcGIS 10.2.2 software based on the topographical charts extracted from IBGE in the 1: 50.000 scale. The raster images were also elaborated from this cartographic base through interpolation methods. The granulometric analyzes were developed at the Soil Erosion Geomorphology Laboratory, Federal University of Uberlândia, using the sieving method. The study area in question pervades the Brasilia Folding Range and the São Francisco Sedimentary Basin, and in this context the objective of this work was to understand the behavior of the channels from the relationship between morphometric aspects and particle size distribution Involved.